Histopathological charaderization of nephritides in the brown capuchin monkey, Cebus apella (Primates: Cebidae) - Borda, Juan T (Universidad de Costa Rica, 2000)
The renal lesions are of special importance in the captive primates. The most eornmonly pathologies are: pyelonephritis, nephrocalcinosis, glomerulonephritis, congenital malforrnations, hydronephrosis and functional diseases. We report the histopathological study of renal lesions of five cases of deaths in Cebus apella (Primates) of the Argentínean Primate Center. The ages of the monkeys were from 4 months to 15 years old. Microscopically, we have observed prineípally acute diffuse proliferative glomerulonephritis, hilar mesangio proliferative glomerulonephritis, extracapilar glomerulonephritis with ereseents, chronie interstitial nephritis and chronie pyelophritis